Sumber Belajar Internet di Pesantren - Putri, Rizkika (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
This article explains how the internet is a learning resource in Islamic boarding schools. This article aims to explain the benefits and negative impacts of the internet as well as solutions for handling them in Islamic boarding schools. Islamic boarding schools have several criteria based on the number of students, based on facilities and infrastructure, and in terms of what is taught. The negative impacts of using the internet as a learning resource are explained in this article, namely; (1) the availability of access to pornographic sites which are feared to damage the morals of the students, (2) then there are entertainment facilities created by the internet, such as online games and social networking sites which can give the students a taste of addiction.